EP-142 Assessing the Diagnostic Sensitivity of CT and Ultrasound in Suspected Appendicitis. (9th August 2022) - Ahmed, Salma; Hassan, Karim; Abubaker, Malaz; Wilson, Jeremy; Magee, Conor
Abstract: Introduction: Acute appendicitis is the most common surgical emergency and accounts for one-third of adult patients presenting to A&E. CT imaging has high positive predictive value for acute appendicitis. Ultrasound, on the other hand, is preferred as a first-line imaging in children and women of child-bearing age. However, it is dependent on operator experience, variation in appendiceal anatomy and patient body habitus. The RCR standards for the CT sensitivity should be >90% and for US it should be >70%. We conducted this study to investigate whether the diagnostic yield of CT and Ultrasound imaging in suspected appendicitis meet that of published research studies. Method: All patients who underwent CT or US for suspected appendicitis followed by confirmed diagnosis where included. RCR AuditLive template was used to assess the performance in our local hospital. Results: Sixty patients included. Of which eighteen had Ultrasound Abdomen and pelvis, forty-six had contrast CT scan and four patients had US followed by CT. Sensitivity for CT and US was 93% and 40% respectively with negative appendectomy rate of nearly 2%. Conclusion: The standards for CT have been met in our hospital, however this is not the case for the US. This could be related to the performing operator, group of patients referred for US or the request itself, weather we request it to confirm the presence of appendicitis or rather excluding other pathologies. In all cases we recommend that we discuss these results in our next joined meeting with the radiologists.